Anti-VEGF treatment switch in real-world DME patients: ranibizumab versus aflibercept for bevacizumab DME non-responding patients (SWIRL study) - Yu Qiang Soh; Zheng Xian Thng; Wei Kiong Ngo; Colin S Tan; Tock Han Lim; Louis W Lim; Augustinus Laude; Darren Choy; Wen Jun Song; Helen Fang Mi; Koh Lilian; Jacob Yu Hang Chin; et al. (BMJ Open Ophthalmology)
Background/aims To describe the functional outcomes of patients with diabetic macular oedema (DME) non-responsive to bevacizumab switched to ranibizumab or aflibercept over 1 year and the demographic and anatomic predictors of these functional outcomes.Methods In a retrospective real-world cohort study, 76 consecutive patients with DME non-responsive to bevacizumab were reviewed at baseline and 12 months after switch to ranibizumab or aflibercept. Visual acuity (VA) and optical coherence tomography features such as central retinal thickness were assessed. Multiple logistic regression was performed to determine predictors for outcomes.Results From baseline to 1 year, the overall best-corrected VA improved by LogMAR 0.015±0.19 with no difference between patients who switched to ranibizumab or aflibercept (LogMAR 0.017±0.21 vs LogMAR 0.013±0.17, p=0.92). Ranibizumab patients had more reduction in central subfield thickness (CST) (390.13 µm vs 334.20 µm, p=0.033) than aflibercept patients. Baseline HbA1c (p=0.012) and number of bevacizumab injections (p=0.040) were significantly associated with gain in VA, while change in CST was a strong predictor of VA change (p<0.01). Aflibercept patients were more likely to gain vision after 6 months but not at 12 months.Conclusions In a real-world study, improvements in functional outcomes can still be gained after switching anti-vascular endothelial growth factor in bevacizumab non-responders. Both ranibizumab and aflibercept were comparable and effective treatments.